Public Administration in the NICs
XIV, 177 p.
Keywords: The four dragons of Asia - Hong Kong, Singapore, Taiwan and South Korea - have achieved remarkable progress over the past decades. These newly industrialising countries (NICs) have emerged as major actors on the world economic scene. Their success can be attributed to a number of factors related to historical background, relationship with China, pattern of governance and performance of administrative, political and economic institutions. This book examines the role of public administration in the accomplishments of the NICs and identifies potential areas of challenge for the dragons.